Bolus Insulin Dose Error Distributions Based on Results From Two Clinical Trials Comparing Blood Glucose Monitoring Systems. (September 2017) - Pardo, Scott; Dunne, Nancy; Simmons, David A.
Background: In 2 previous clinical trials, fingertip capillary blood samples were evaluated using prespecified blood glucose monitoring systems (BGMSs) and a reference YSI glucose analyzer. In post hoc analyses, hypothetical insulin doses were calculated using these blood glucose measurements; dosing errors were compared for each trial. Method: For each blood glucose measurement, premeal bolus insulin dosing was determined for a hypothetical person, assuming a 60-g carbohydrate meal and 100-mg/dL target blood glucose level (adjusting 1/25 insulin sensitivity and 1/15 insulin:carbohydrate ratio inputs to account for BGMS measurement error). Dosing error was the difference between doses calculated using the BGMS and YSI results. Results: In Clinical Trial 1, 95% dose error ranges (in units of insulin) were: CONTOUR ® NEXT EZ BGMS (EZ), –0.9 to 0.5; Accu-Chek ® Aviva BGMS (ACA), –0.5 to 1.8; FreeStyle Freedom Lite ® BGMS (FFL), –3.2 to −0.3; OneTouch ® Ultra ® 2 BGMS (OTU2), –4.1 to 0.3; and Truetrack ® BGMS (TT), –3.9 to 2.2. In Clinical Trial 2, these ranges were: CONTOUR ® NEXT BGMS (CN), –0.7 to 1.7; Accu-Chek ® Aviva Nano BGMS (ACAN), –1.3 to 1.8; FreeStyle Lite ® BGMS (FSL), –5.1 to 0.2; OTU2, –1.9 to 1.2; OneTouch ® Verio ® Pro BGMS (OTVP), –1.0 to 1.9; and TT, –5.1 to 1.7. Within each trial, EZ and CN had statistically significantly smaller insulin dose error ranges than other BGMSs ( P <0.0001). Conclusions: The ranges of insulin dose errors were statistically significantly smaller with EZ and CN than with all other BGMSs in this post hoc analysis. Differences in BGMS accuracy could result in clinically important differences in insulin dosing.